Incomprehension, dependency, and distrust in the presentation of fixed asset figures: Front stage dramaturgy - Eka Findi Tresnawati; Ali Djamhuri; Ari Kamayanti (Universitas Hayam Wuruk Perbanas, 2016)
This study aims to explore the role of actors in presenting financial statements and those who manage assets in performing the presentation of fixed assets figures in the balance sheet. These actors consist of the major parts in various stories. Dramaturgy was employed as a method to analyze the roles, coupled with an analysis of impression management from John and Pittman Taxonomy. A thorough research review was conducted on the front stage. In some scenes, the actors performed intimidation when forcing other actors to present the asset data instantly. In another time, ingratiation was done to cover the weak-nesses when the assets caretaker felt neglected. The role of self-promotion was performed by the Financial Manager of Regional Work Unit (PPK-SKPD) when he wanted to show that he had worked hard to prepare the balance sheet and refuses to bear the errors when the balance sheet presenting assets data was in trouble. Impression management techniques were used entirely by the actors to show the desired self-image, at certain time and in cer-tain circumstances. The roles played by the actors give rise to the phenomenon that the fixed assets figures presented in the balance sheet rest on the condition of incomprehension, dependency, and distrust between the actors. The presentation of fixed assets figures in the balance sheet shows a series of accounting process filled by conflict, as seen throughout the show. This research is expected to increase the study in the context of academic on the topic of fixed assets, particularly in the public sector (government).